Citotoxicidade e potencial efeito antitumoral in vitro da organotelurana RF07(4- {2-Cloro-3-[clorometilideno]-1-oxa-2-( λαμβδα)4-teluraspiro [3.5]non-2-il}fenil Metil Éter) em células de adenocarcinoma mamário humano - Castro, Isione Oliveira (2024)
Breast cancer is the most prevalent type of cancer and the leading cause of mortality among women. Chemotherapy is the most commonly used treatment modality, but it has limitations, mainly due to high toxicity and the development of drug resistance. Considering that organotelluranes show antitumor potential, the aim of this study was to further investigate the cytotoxicity and in vitro antitumor effects of the organotellurane RF07 in the human breast adenocarcinoma cell line MCF-7. Cytotoxicity was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay in human tumor (MCF-7) and non-tumor (MCF10A) breast cells. RF07 exhibited a median inhibitory concentration (IC50) of 3.3 ± 0.08 µM and 21.16 ± 0.9 µM for MCF-7 and MCF-10A, respectively, after 72 hours of treatment, showing a 6-fold selectivity for the tumor cell line (SI: 6.41). To evaluate the mechanisms of action of RF07, its effects on the cell cycle, apoptosis, production of reactive oxygen species (ROS), and cytotoxic potential in tumor spheroids were investigated. RF07 altered cell cycle progression, increasing the percentage of cells in the S phase and in the sub-G1 fraction after 48 hours of treatment. There was an increase in the percentage of apoptotic cells, detected by flow cytometry after cell staining with annexin V-FITC and propidium iodide (PI). Microscopic analyses confirmed the apoptotic effect of RF07, showing indicative morphological characteristics such as nuclear alterations (condensed and/or fragmented chromatin) and changes in mitochondrial membrane permeability. Pre-treatment with N-acetyl-Lcysteine (NAC) significantly prevented cytotoxicity, suggesting that RF07 induces cytotoxicity through ROS production. Additionally, RF07 reduced the size and migration radius of tumor spheroids, confirming its cytotoxic action in this experimental model. In conclusion, the results indicate that RF07 exhibits in vitro antitumor activity in human breast adenocarcinoma MCF-7 cells, promoting cell cycle alterations, increased production of reactive oxygen species, and inducing apoptosis.